Pig’s Feet: An Autoethnography of Weight-Based Discrimination - Saville, Amber (Cuizine, 2025)
Using autoethnography, this paper examines my experiences in public school and a medical encounter as these were shaped through my disability and an eating disorder. I explore themes of fat stigma, fat shaming and weight-based discrimination. Autoethnography is a research method that connects and critically reflects on personal narratives with wider cultural and social phenomenon. Through writing about my own embodied experiences, I employ the concept of healthism, which contends that individuals are responsible for their own health. Health is broadly understood in the socio-historical contexts of the childhood "obesity epidemic" and the thin ideal. Through my analysis I show how weight-bias and fat stigma lead to fat shaming and healthcare avoidance.